Translating Tagore's stray birds into Chinese : applying systemic functional linguistics to Chinese poetry translation /: applying systemic functional linguistics to Chinese poetry translation. (2020) - Ma, Yuanyi; (Professor of translation studies), Wang, Bo
No abstract available